2021
DOI: 10.14715/cmb/2021.67.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Tinospora cordifolia (Willd.) Miers: phytochemical composition, cytotoxicity, proximate analysis and their biological activities

Abstract: The present research work has been performed to evaluate the phenolic content, flavonoids content, and cytotoxicity of a multidimensional medicinal plant; Tinospora cordifolia and as well as to determine nutritive value by proximate analysis. The total phenolic and flavonoids contents of Tinospora cordifolia were found to be significantly greater in methanol extract as compared to corresponding hexane extract. Brine shrimp bioassay indicated Tinospora cordifolia is pharmacologically active. The percentage comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…They recorded that CCl 4 and CHCl 3 soluble fractions showed highly cytotoxic in Artemia salina with LC 50 values of 0.402 and 0.691 μg/mL [60]. Likewise, in 2021, Modi and coworkers documented that ethanol stem and leaves extract of T. c o r d i f o l i a had a cytotoxic effect in A. salina with LC 50 values of 462.38 and 676.08 μg/mL [61]. Furthermore, Jagetia and Rao studied the cytotoxic effects of DCM extract of T. cordifolia on cultured HeLa cells.…”
Section: Cytotoxic Activity Of Menispermaceaementioning
confidence: 99%
“…They recorded that CCl 4 and CHCl 3 soluble fractions showed highly cytotoxic in Artemia salina with LC 50 values of 0.402 and 0.691 μg/mL [60]. Likewise, in 2021, Modi and coworkers documented that ethanol stem and leaves extract of T. c o r d i f o l i a had a cytotoxic effect in A. salina with LC 50 values of 462.38 and 676.08 μg/mL [61]. Furthermore, Jagetia and Rao studied the cytotoxic effects of DCM extract of T. cordifolia on cultured HeLa cells.…”
Section: Cytotoxic Activity Of Menispermaceaementioning
confidence: 99%
“…In one study, the alkaloid berberine was found to inhibit the enzyme phospholipase A2, which is responsible for the release of venom from the fangs of snakes. The flavonoids present in the plant have been shown to have antioxidant, anti-inflammatory, and anti-venom properties 100 . Several flavonoids, such as quercetin and kaempferol, have been found to inhibit the enzyme hyaluronidase, which is responsible for the spread of venom in the body.…”
Section: Phytochemical Constituents and Its Medicinal Propertiesmentioning
confidence: 99%
“…The methanol extract from the leaves and stem of Tinospora cordifolia from Ilam District of Nepal, exhibited elevated Total Phenolic Content (TPC) and Total Flavonoid Content (TFC) as compared to the hexane extract. This suggests a greater efficiency in extracting polar compounds by using a polar solvent (Modi, Koirala, et al, 2021). The secondary metabolites present in the plant can vary even within the same plant due to differences in sampling methods, analysis of plant parts, solvents used for extraction, harvest time, storage, growing climate conditions, genetic factors, and many more (Aryal et al, 2021).…”
Section: Figure 1 Gallic Acid Standard Curve (765 Nm)mentioning
confidence: 99%